Krajowy system ratowniczo-gaśniczy w systemie bezpieczeństwa wewnętrznego państwa - Ręcławowicz, Stanisław; Wrzesiński, Janusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
National Firefighting and Rescue System was formed on 1 January 1995 under the Act of 24August 1991. The Act, which initiated achange in our state internal security system, changing its paramilitary character into civilian. Despite the laws of abygone era of communism the creation of the State Fire Service as aseparate formation within the Ministry of Internal Affairs allowed „the exclusion” of organizational units of the fire brigade of the Civil Defence so-called „rescue units group”.This formation was obliged to create the National Rescue and Fire Fighting, possessing the power switch to the system of other units of fire protection services, inspections, internships, institutions and entities that voluntarily on the basis of acivil contract agreed to cooperate in rescue operations.This system gives permission to the Chief Commander in the State Fire Service, Provincial and District Heads to determine respectively in the country, province or district the tasks, coordinate operation and manage it in extreme situation.The Provincial Governor and the District Head carry out their tasks with the appropriate provincial and district crisis management team, operating under the Act of 26 April 2007. Crisis Management Dz.U. Journal of Laws No. 89, item. 590, as amended. Amendment 2.The Village Head has the authority supervised by the mayor or city president, who coordinates the operation of the National Firefighting and Rescue System within the municipality to the extent determined by the Provincial Governor. In other words, the system enables the interaction of organizational units of government, local government, private entities and public benefit organizations.The relevant Governors play ameaningful role in this system. They perform tasks and powers of the State Fire Service with the help of provincial commanders of the State Fire Service in the province.
Keywords: system ratowniczo-gaśniczy; bezpieczeństwo wewnętrzne